1. The problem statement, all variables and given/known data Hello! Please, take a look at the following equation and help me to understand where the authors got the value of φ = π/3. I don't see where it is derived from as no additional conditions are given. 2. Relevant equations x(t) = 5e(-t/5) cos(t) + 5e(-t/5) √3 sin(t) 3. The attempt at a solution Here is how I proceed: x(t) = 5e(-t/5) (cos(t) + √3 sin(t)) Now, given the formula: f(x) = a sin(wx) + b cos(wx) + B (w > 0) is the same as f(x) = √a2+b2 sin(wx + φ) + B In my case, B = 0, so I rewrite the expression as: x(t) = 5e(-t/5) ( √3 sin(t) + cos(t) ) x(t) = 5e(-t/5) √√32+12 sin(t + φ) x(t) = 10e(-t/5) sin(t + φ) But in the book they have: x(t) = 10e(-t/5) sin(t + π/3) Where did they get φ = π/3 from? Thank you!